Spontaneous rupture of the non-gravid uterus. (11th April 2013) - Weng, Leong Chee; Menon, Tulsi; Hool, Graham
Abstract : A 71-year-old woman presents with acute onset abdominal pain with sepsis. Initial workup with an abdominal CT scanning revealed intraperitoneal air with an enlarged uterus and thickened small bowel loops. Haemodynamic instability with sepsis prompted urgent laparotomy. At laparotomy, spontaneous perforation of the uterus was identified. The cause was due to infarction of the myometrium. This occurred on a background of not having any previous instrumentation of the uterus.